The Anti-inflammatory Mediator Resolvin E1 Protects Mice Against Lipopolysaccharide-Induced Heart Injury - Zhang, Jishou; Wang, Menglong; Ye, Jing; Liu, Jianfang; Xu, Yao; Wang, Zhen; Ye, Di; Zhao, Mengmeng; Wan, Jun (Frontiers in Pharmacology, 2020)
Background Sepsis-induced cardiomyopathy (SIC) is a common severe complication of sepsis that contributes to mortality. SIC is closely associated with excessive inflammatory responses, failed inflammation resolution, and apoptotic damage. Resolvin E1 (RvE1), an omega-3 polyunsaturated fatty acid (PUFA)-derived metabolite, has been reported to exert anti-inflammatory or proresolving activity in multiple animal models of inflammatory disease. However, the therapeutic potential of RvE1 in SIC remains undetermined, which was, therefore, the aim of the present study. Methods C57BL/6J mice were randomly divided into three groups: control, lipopolysaccharide (LPS), and LPS + RvE1. Echocardiography, Western blotting (WB), quantitative real-time (QRT)-PCR, histological analyses, and flow cytometry were used to evaluate cardiac function, myocardial inflammation, and the underlying mechanisms. Results The RvE1-injected group showed improved left ventricular (LV) function and reduced serum lactate dehydrogenase (LDH) and creatine kinase myocardial bound (CK-MB) levels. Compared to LPS treatment alone, RvE1 treatment inhibited the infiltration of neutrophils and macrophages into the heart and spleen and suppressed the secretion of pro-inflammatory cytokines, including interleukin (IL)-1β, IL-6, and monocyte chemoattractant protein (MCP)-1, in the heart. We also observed that the activation of the mitogen-activated protein kinase (MAPK) and nuclear factor (NF)-κB signaling pathways was blocked by RvE1 treatment, and this inhibition contributed to the improvement in the inflammatory response induced by LPS. RvE1 inhibited LPS-induced M1 macrophage polarization and promoted macrophage polarization toward the M2-like phenotype in both the heart and spleen. In addition, LPS administration dysregulated cyclooxygenase (COX) and lipoxygenase (LOX) in the heart, which were rectified by RvE1 treatment. RvE1 also reduced myocardial apoptosis rate in response to LPS-induced heart injury. Conclusion RvE1 protects the heart against SIC possibly through the inhibition of the MAPK and NF-κB inflammatory signaling pathways, modulation of macrophage polarization, and reduction in myocardial apoptosis. RvE1 may be a novel lipid mediator for the treatment of SIC.